Gestión administrativa y su relación con el desempeño laboral en la Unidad de Gestión Educativa Local - Nauta, 2022 - Ochoa del Aguila, Manuel Alberto (2023)
The objective of this study is to know how administrative management and job performance are related at UGEL Nauta, 2022. The study is descriptive with a quantitative approach. The survey data was calculated to have a Pearson correlation value of 0.885**, showing that variables 1 and 2 have a strong positive relationship, however, it has a significant degree and a two-sided (two-sided) sigma value. of 0.000; as the decision rule states, Ha will be accepted if the calculated Sigma value is less than 0.05. The hypothesis, which states that there is a significant correlation between the organizational climate and the work performance of employees, is based on the value achieved.